Market of Lily Bulbs in Argentina - Marinangeli, Pablo Alejandro (2011)
In Argentina more than 91% of lily bulbs are produced as cut flowers and the rest as pot plants and dry sales. Flower producers import their bulbs or purchase them from retailers, although in this case the prices are often higher. 91% of the bulbs are imported from Europe, mainly The Netherlands, and are usually transported by ship. 9% are obtained from Chile and transported by truck. Argentinean imports of lily bulbs increased significantly until 2001, followed by a drastic decrease due to the deep devaluation of the Argentinean currency in 2002. This resulted in increased costs of crop production and depressed the demand. However, imports rose again starting from 2005 up to 2009, reaching 6.3 million bulbs. This surpassed the value of bulbs imported in 2001. Although the quantity of imported bulbs increased, the number of importers decreased from 9 in 2001 to 4 in 2008, showing a concentration of the market. In 1999 Asiatic and Oriental hybrids were widely cultivated with a smaller proportion of L. longiflorum × Asiatic (LA) hybrids and L. longiflorum cultivars. At the present time, LA, Oriental × Trumpet (OT) and Oriental hybrids are the top choices, followed in a smaller proportion by the Asiatic, L. longiflorum × Oriental (LO) and L. longiflorum hybrids. The market of lily cut flowers and pot plants in Argentina is expanding, and bulb imports and local production are expected to increase. A comparison with the lily market in the neighboring countries is presented.